2022
DOI: 10.3389/fmicb.2022.1020932
|View full text |Cite
|
Sign up to set email alerts
|

The two-component regulatory system CenK–CenR regulates expression of a previously uncharacterized protein required for salinity and oxidative stress tolerance in Sinorhizobium meliloti

Abstract: Genes of unknown function constitute a considerable fraction of most bacterial genomes. In a Tn5-based search for stress response genes in the nitrogen-fixing facultative endosymbiont Sinorhizobium (Ensifer) meliloti, we identified a previously uncharacterized gene required for growth on solid media with increased NaCl concentrations. The encoded protein carries a predicted thioredoxin fold and deletion of the gene also results in increased sensitivity to hydrogen peroxide and cumene hydroperoxide. We have des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…7A ), as has been reported for some other TCSs ( 78 - 80 ) including ones that control cell envelope processes in other bacteria ( 81 , 82 ). Moreover, we propose that the basal, and likely constitutive, activity of CenKR contributes to the essentiality of this TCS in other α-proteobacteria ( 25 , 39 , 83 ).…”
Section: Discussionmentioning
confidence: 89%
“…7A ), as has been reported for some other TCSs ( 78 - 80 ) including ones that control cell envelope processes in other bacteria ( 81 , 82 ). Moreover, we propose that the basal, and likely constitutive, activity of CenKR contributes to the essentiality of this TCS in other α-proteobacteria ( 25 , 39 , 83 ).…”
Section: Discussionmentioning
confidence: 89%
“…CenR was first described as an essential RR in C. crescentus , where it functions to regulate cell envelope structure (34), and is now known to be conserved in many alphaproteobacterial orders (33). Recent work has shown that cenR is essential in R. sphaeroides , where it controls transcription of the Tol-Pal outer membrane complex and other cell envelope genes (33), and in Sinorhizobium meliloti where it mediates osmotolerance and oxidative stress resistance (32). In all three of these species, CenR is regulated by a cognate histidine kinase, CenK.…”
Section: Discussionmentioning
confidence: 99%
“…Through a series of genetic, genomic, and biochemical experiments, we uncovered evidence for direct cross-regulation between these three TCS proteins, which control transcription of a common gene set to support B. ovis replication under envelope stress conditions and in the host intracellular niche. Specifically, the conserved alphaproteobacterial cell envelope regulator, CenR (32)(33)(34), stimulates phosphoryl transfer between the cognate RR-HK pair, EssR-EssS, while CenR and EssR regulate the steady-state levels of each other in B. ovis. Our results expand understanding of molecular mechanisms of two-component signal transduction and define an unusual mode of TCS crossregulation in Brucella that controls gene expression to support envelope stress resistance and intracellular replication.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other possible explanations, not mutually exclusive, can also account for JspA's involvement in resistance against cell envelope assaults: for example, JspA may degrade other substrates or signaling pathways under specific conditions, or JspA and LppA may assist in the proper construction of the cell envelope by ensuring proper maturation of other lipoproteins. Furthermore, a number of other signaling systems, such as ActK-ActJ, CenK-CenR, CpxA-CpxR, EmmB-EmmC, FeuQ-FeuP, and NtrX-NtrY, contribute to the maintenance of cell envelope integrity in rhizobia (Albicoro et al, 2021;Albicoro et al, 2023;Bensig et al, 2022;Calatrava-Morales et al, 2017;Lakey et al, 2022;Morris & Gonzalez, 2009;Santos et al, 2010;VanYperen et al, 2015;Wang et al, 2013;Xing et al, 2022), and how these different systems cooperate with ExoS-ChvI to ensure successful symbiosis remains ripe for further investigation.…”
Section: Discussionmentioning
confidence: 99%